Modern approaches to the surgical treatment of spinal injuries - Radchenko, Volodymyr; Popsuishapka, Olexii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with our experience in the surgical treatment of spinal injuries. One hundred and forty-six patients with injuries of their cervical, thoracic and lumbar spine served as the material for the study. The tactics of the surgical treatment was based on the principles of “AO Spine International”, namely: reduction, decompression, stabilization, prophylaxis of the affection of adjacent segments, and early patients’ activation. The complex early diagnosis of spinal injuries and the differentiated opportune surgical treatment make it possible to improve functional outcomes, as well as to decrease the number of possible complications.